From pattern to process: studies at the interface of gene regulatory networks, morphogenesis, and evolution. (August 2018) - Smith, Sarah Jacquelyn; Rebeiz, Mark; Davidson, Lance
Abstract : The development of anatomical structures is complex, beginning with patterning of gene expression by multiple gene regulatory networks (GRNs). These networks ultimately regulate the activity of effector molecules, which in turn alter cellular behavior during development. Together these processes biomechanically produce the three-dimensional shape that the anatomical structure adopts over time. However, the interfaces between these processes are often overlooked and also include counter-intuitive feedback mechanisms. In this review, we examine each step in this extraordinarily complex process and explore how evolutionary developmental biology model systems, such as butterfly scales, vertebrate teeth, and the Drosophila dorsal appendage offer a complementary approach to expose the multifactorial integration of genetics and morphogenesis from an alternative perspective.